2013
DOI: 10.1371/journal.pmed.1001417
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Coverage in MNCH: Accuracy of Measuring Diagnosis and Treatment of Childhood Malaria from Household Surveys in Zambia

Abstract: BackgroundTo assess progress in the scale-up of rapid diagnostic tests and artemisinin-based combination therapies (ACTs) across Africa, malaria control programs have increasingly relied on standardized national household surveys to determine the proportion of children with a fever in the past 2 wk who received an effective antimalarial within 1–2 d of the onset of fever. Here, the validity of caregiver recall for measuring the primary coverage indicators for malaria diagnosis and treatment of children <5 y ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
58
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 13 publications
0
58
0
Order By: Relevance
“…Prior research has shown that vital registry data underestimate under-5 mortality compared with data obtained from household surveys, 18 and in our study the HMIS data likely capture only about half of all child deaths. While national household-based birth history data are available from the 2010 Rwanda DHS, this survey provides only a 5-year average of national under-5 mortality, not district-level, monthly totals of under-5 deaths, which are needed to examine the impact of iCCM in the first year of implementation in each district 38 . Although our community-based HMIS data likely underestimate under-5 deaths, we expect them to underestimate deaths similarly in both the baseline and implementation periods.…”
Section: Discussionmentioning
confidence: 99%
“…Prior research has shown that vital registry data underestimate under-5 mortality compared with data obtained from household surveys, 18 and in our study the HMIS data likely capture only about half of all child deaths. While national household-based birth history data are available from the 2010 Rwanda DHS, this survey provides only a 5-year average of national under-5 mortality, not district-level, monthly totals of under-5 deaths, which are needed to examine the impact of iCCM in the first year of implementation in each district 38 . Although our community-based HMIS data likely underestimate under-5 deaths, we expect them to underestimate deaths similarly in both the baseline and implementation periods.…”
Section: Discussionmentioning
confidence: 99%
“…From a measurement perspective, estimates of gender imbalances in child illness and treatment based on parental reports may be inaccurate. Previous studies have already documented that parents do a poor job at distinguishing diseases in their children, 34 and also that recall periods have a biasing effect on illness reporting. 35 Parental reports collected as part of the DHS are a primary means for estimating illness prevalence among children in developing countries, but alternative or supplementary methods should perhaps be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Positive RDT rates were the highest among febrile cases reporting to CHWs for treatment (Hamainza et al, 2014). Introduction of RDT and ACT consumption led to a large decline in reported malaria cases in parts of Zambia Eisele et al, 2013). Rapid diagnostic test was used to diagnose malaria for 98.3% cases in some clinics (Eisele et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of RDT and ACT consumption led to a large decline in reported malaria cases in parts of Zambia Eisele et al, 2013). Rapid diagnostic test was used to diagnose malaria for 98.3% cases in some clinics (Eisele et al, 2013). A higher proportion of laboratory tests confirmed by microscopy (67.4%), as opposed to clinically diagnosed malaria, was reported in one district in Zambia (Eisele et al, 2013) and it is felt that the use of RDTs in the diagnosis of malaria will affect national (and global) malaria control strategies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation